No Friend of Mine - Turnbull, Ann (Walker Books Ltd, 1994)
Lennie's family lives in a poor English mining town in 1937, and when he and the son of the wealthy mine owner become friends, Lennie's feelings of camaraderie are complicated by class conflicts and envy.
Keywords: Europe; Juvenile Fiction; People & Places